2018
DOI: 10.1080/2162402x.2018.1534664
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib sensitizes multiple myeloma to NK cells via ER-stress-induced suppression of HLA-E and upregulation of DR5

Abstract: Although the proteasome inhibitor bortezomib has significantly improved the survival of patients with multiple myeloma (MM), the disease remains fatal as most patients eventually develop progressive disease. Recent data indicate that MM cells can evade bortezomib-induced cell death by undergoing autophagy as a consequence of endoplasmatic reticulum (ER)-stress induced by proteasome inhibition. Here we show that bortezomib sensitizes MM cells to NK cell killing via two distinct mechanisms: a) upregulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…A few studies have reported that endoplasmic reticulum (ER) stress results in posttranscriptional downregulation of surface HLA-E, but not of classical HLA-I levels. It was postulated that this selective loss of HLA-E may be due to HLA-E having a less stable tertiary structure than other classical HLA-I molecules and, thus, a shorter half-life at the plasma membrane (79). So far, few studies have investigated ER stress specifically in HIV-1, but it has been shown that an unfolded-protein response can be detected following in vitro HIV-1 infection of primary PBMCs (80).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported that endoplasmic reticulum (ER) stress results in posttranscriptional downregulation of surface HLA-E, but not of classical HLA-I levels. It was postulated that this selective loss of HLA-E may be due to HLA-E having a less stable tertiary structure than other classical HLA-I molecules and, thus, a shorter half-life at the plasma membrane (79). So far, few studies have investigated ER stress specifically in HIV-1, but it has been shown that an unfolded-protein response can be detected following in vitro HIV-1 infection of primary PBMCs (80).…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no experimental evidence to date in any preclinical model or human tumor specimens linking either dopamine or dopamine receptors to the immune stimulatory effects of ONC201. Also, ISR activation [45] , [46] , [47] and PI3K/Akt inhibition [48] have been associated with activation of NK cell cytotoxicity and sensitization of tumors cells to NK cells. The relevance of these aspects of the ONC201 mechanism of action for immune activation remains to be evaluated.…”
Section: Onc201 Mechanism Of Actionmentioning
confidence: 99%
“…We have examined the clinical effects of ex vivo -expanded autologous NK cells in concert with treatment with the proteasome inhibitor bortezomib (ClinicalTrials.gov: NCT00720785 ), 7 which has been shown to sensitize tumors to NK cell cytotoxicity. 8 , 9 NK cells also contribute to the efficacy observed with monoclonal biologics such as rituximab, as genetic variants of the NK cell receptor CD16, which mediates antibody-dependent cytotoxicity, correlate with anti-tumor responses. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%